ENT600: Portable water sampling kit / Wan Muhamad Norazwan Wan Abu Bakar, Mohd Azmieludin Mohd Suhaimi and Nik Muhammad Hanif Nik Man - Wan Abu Bakar, Wan Muhamad Norazwan; Mohd Suhaimi, Mohd Azmieludin; Nik Man, Nik Muhammad Hanif (2017)
Water quality unit is one of the main scopes of Environmental Health Officer in Health District Office. They need to maintain a good water quality especially drinking water for all the people in this country have a good water supply from the water consortium for their state for example Air Selangor (AIS) that before this known as Syarikat Bekalan Air Selangor (SYABAS). The company needs to follow, Malaysia Drinking Water Quality Standard such as limitational of chlorine in water from sampling station is below than 2 and higher than 0.2. The main objective of water quality unit is to elevate the health of the public by ensuring that the supplied drinking water is safe and acceptable to the consumers. This can be achieved through an effective regulatory program by reducing the occurrence of epidemic or poisoning associated with the unsatisfactory supply of water. This program ensures that health personnel informs the Water Department and Water Company immediately about quality violations set by the Health Ministry and are ready to take a recovery step before the onset of a disease or water borne poisoning. If there are some parameter from the sample not follow the national limit standard, Environmental Health Officer (EHO) will issue a Correction Report (CR) for the water consortium to check their treatment plant. The main goal of this project is to create a portable water sampling unit that can run the test for all three physical parameter of water that is residue for chlorine, the temperature of water, Ph of the water, and water turbidity. Nowadays, EHO needs to carry 3 larger sampling unit that tests all of this parameter. With this project, they don't need to waste their time and energy to bring a lot of machines and can finish the job faster than usual. This project also can reduce the cost for maintenance or calibration for 3 machines than 1 that will be created. The durability of this product also become the main objective for the company. This product can be used without calibration longer than usual.